2021
DOI: 10.3389/fncir.2021.741767
|View full text |Cite
|
Sign up to set email alerts
|

Disorganization of Oscillatory Activity in Animal Models of Schizophrenia

Abstract: Schizophrenia is a chronic, debilitating disorder with diverse symptomatology, including disorganized cognition and behavior. Despite considerable research effort, we have only a limited understanding of the underlying brain dysfunction. In this article, we review the potential role of oscillatory circuits in the disorder with a particular focus on the hippocampus, a region that encodes sequential information across time and space, as well as the frontal cortex. Several mechanistic explanations of schizophreni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 379 publications
(584 reference statements)
1
3
0
Order By: Relevance
“…Synaptic plasticity alters the strength of information flow between presynaptic and postsynaptic neurons, thereby regulating the likelihood that APs in presynaptic neurons lead to APs in postsynaptic neurons (Kallupi et al, 2014). Consistently, our results showed that the amplitude of EPSCs in the CA1 region declined in MIA offspring, suggesting the disruption of postsynaptic information processing (An and Sun, 2017b;Speers and Bilkey, 2021). It has been demonstrated that NMDARdependent intrinsic excitability in CA1 pyramidal neurons from MIA offspring was markedly reduced, which caused the detrimental effect on spatial memory impairments (Escobar et al, 2011;Zeraati et al, 2021).…”
Section: Discussionsupporting
confidence: 81%
“…Synaptic plasticity alters the strength of information flow between presynaptic and postsynaptic neurons, thereby regulating the likelihood that APs in presynaptic neurons lead to APs in postsynaptic neurons (Kallupi et al, 2014). Consistently, our results showed that the amplitude of EPSCs in the CA1 region declined in MIA offspring, suggesting the disruption of postsynaptic information processing (An and Sun, 2017b;Speers and Bilkey, 2021). It has been demonstrated that NMDARdependent intrinsic excitability in CA1 pyramidal neurons from MIA offspring was markedly reduced, which caused the detrimental effect on spatial memory impairments (Escobar et al, 2011;Zeraati et al, 2021).…”
Section: Discussionsupporting
confidence: 81%
“…Therefore, it is not surprising that animal models of SZ displays aberrant oscillatory activity in the PFC (Uhlhaas and Singer, 2010;Senkowski and Gallinat, 2015;Hunt et al, 2017). Several of these prefrontal oscillatory alterations observed in SZ patients have been also found in animal models of SZ (Speers and Bilkey, 2021). For example, it have been observed decreased prefrontal gamma oscillations in models of impaired E/I balance (Pinault, 2008;Ahnaou et al, 2017;Ma et al, 2018), in the MAM neurodevelopmental model and the genetic models as Dlx5/6 +/− , DISC1-mutant mice and Arc/Arg3.1 deficient mice (Cho et al, 2015;Gao et al, 2019;Sauer and Bartos, 2022).…”
Section: Prefrontal Oscillations and Functional Connectivity In Schiz...mentioning
confidence: 97%
“…The combination of these hypotheses into an integrative vulnerability-stress model (known as a “two-hit model”), which combines genetic with pre- and postnatal environmental factors, has become one of the most accepted postulates for the development of SZ, which also reveals the complexity and interaction of several factors in its physiopathology ( Bayer et al, 1999 ; Davis et al, 2016 ). Thus, considering these hypotheses, together with the most relevant factors for the development of SZ, several rodent models have been developed ( Table 1 ), in which cognitive impairments are usually evident ( Lipska and Weinberger, 2000 ; Marcotte et al, 2001 ; Jones et al, 2011 ; Winship et al, 2019 ; Speers and Bilkey, 2021 ). For example, neurodevelopmental models, such as prenatal administration of methylazomethanol (MAM) ( Lodge and Grace, 2009 ) display impairments in several cognitive functions, including cognitive control ( Kállai et al, 2020 ).…”
Section: Dysfunctional Activity Patterns In the Mpfc In Mental Condit...mentioning
confidence: 99%
“…Electroencephalography (EEG) monitors electrical brain activity in sleepy or awake animals. Analysis of the waveforms can increase knowledge about brain functionality, providing suitable electrical biomarkers to detect a disorder or to follow its progression (Levenstein et al, 2017 ; Trenado et al, 2019 ; Girardeau and Lopes-dos-Santos, 2021 ; Speers and Bilkey, 2021 ).…”
mentioning
confidence: 99%